Land use and its impact on the Succulent Karoo - Jonas, Zuziwe (Plant Conservation Unit (PCU), 2024)
The Succulent Karoo biome (SK biome) is one of the 25 internationally recognized biodiversity hotspots in South Africa with approximately 1940 endemic species. The SK biome is, however, poorly conserved with less than 5% of the area under formal protection. It is also highly threatened by a range of different land use practices. Considering the lack of protected areas and the high levels of endemism (about 40%), which characterize the region, the current and future land use practices are likely to be the key factors in determining the future conservation of the area. Understanding the land use pattern and its drivers that have occurred in the SK biome provides a useful starting point for outlining the future research needs and establishing conservation goals. This project investigates a range of different land use practices such as urban settlement, mining, cropland, conservation and livestock production with their associated environmental drivers. The study used a Geographical Information System (GIS) to map the current extent of land use practices based on available data from different sources in the SK biome. The study also mapped the current extent of livestock density in two land tenure systems (private and communal) of Namaqualand and developed a statistical model to assess the future agricultural potential in the SK biome. The current status of the land use practices in the SK biome shows that most of its area is used for extensive grazing (90%) followed by conservation (4.8%). Due to the aridity of the area, agriculture potential is low. The results confirmed that the conservation status of the SK biome is relatively low but improving, with 4.8% of the biome conserved. Only 3.5%, however, is formally protected in statutory reserves. The remaining conserved area (1.3%) is conserved in non-statutory reserves.